2020
DOI: 10.14238/pi60.3.2020.149-53
|View full text |Cite
|
Sign up to set email alerts
|

Impact of albumin levels on clinical outcomes in children underwent abdominal surgery

Abstract: Background Patients underwent abdominal surgery and had hypoalbuminemia were at risk of post-operative complications. The prognostic role of albumin levels in children with abdominal surgery remains unclear. Objective To investigate the impact of albumin levels on clinical outcomes related to the complications in children with abdominal surgery. Methods This was a retrospective cohort study on children aged 29 days to 18 years, who underwent abdominal surgery, had serum albumin levels measured at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This finding is close to a prior report which concluded that hypoalbuminemia in children undergoing abdominal surgery is linked to the increased risk of postoperative longer hospital LOS. 40 Additionally, preoperative serum albumin showed inverse significant correlations with both preoperative TLC and CRP, a relation which is close to a previous report which yielded that there was a persistent elevation of systemic inflammatory blood-borne markers (TLC and CRP) with a continued persistent reduction in albumin in patients who had undergone esophageal resections. 41 Additionally, the role of GPS was also investigated in infections.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is close to a prior report which concluded that hypoalbuminemia in children undergoing abdominal surgery is linked to the increased risk of postoperative longer hospital LOS. 40 Additionally, preoperative serum albumin showed inverse significant correlations with both preoperative TLC and CRP, a relation which is close to a previous report which yielded that there was a persistent elevation of systemic inflammatory blood-borne markers (TLC and CRP) with a continued persistent reduction in albumin in patients who had undergone esophageal resections. 41 Additionally, the role of GPS was also investigated in infections.…”
Section: Discussionsupporting
confidence: 88%
“…Dewi et al reported that preoperative albumin levels of ≤3.0 g/dL were predictors of increased risk of postoperative complications, such as sepsis and the need for relaparotomy. 6 A study also reported that a preoperative albumin level of 2.5 -3.45 g/dL predicts an increased risk of postoperative abdominal surgical site infection complications. 10 Albumin serves a vital biological function in the body, specifically in maintaining plasma oncotic pressure and transporting bilirubin, fatty acids, and drugs.…”
Section: Discussionmentioning
confidence: 96%
“…This figure was lower compared to that of another study (36.3%). 6 We discovered that severe acute malnutrition was a significant prognostic factor for the occurrence of postoperative complications. Similarly, a study conducted at the same hospital on children who underwent laparotomy reported that 57.1% of pediatric patients with poor nutritional status experienced postoperative complications or death.…”
Section: Discussionmentioning
confidence: 99%